Pelatihan Business Pitching Bagi Pelaku UMKM Dalam Menarik Minat Investor - S, Yulia Sariwaty; Azhar, Dimas Akhsin; Retnasary, Maya; Rahmayani, Rani; Ngare, Ferdinandus (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2025)
Micro, Small and Medium Enterprises (in Indonesia it’s known as UMKM) are one of the pillars of the Indonesian economy, their existence contributes greatly to the national GDP. The downturn experienced by UMKM during the pandemic did not last long, many new strategies and innovations emerged to create new business ideas and opportunities. However, this is still hampered by capital problems. The government in collaboration with banks has provided access to capital assistance for UMKM players through the people's business credit policy. Several state-owned companies have also opened opportunities to provide capital loans including business assistance for UMKM as a form of Corporate Social Responsibility, but in an effort to apply for business capital loans, business actors must have the ability to convince financiers or investors about the business or business they will do. Business pitching training for UMKM was organised to provide learning for participants to be able to present and convince investors of their business ideas. The training was carried out using a seminar method for material briefing followed by a workshop as a form of practice of the material that had been received. All participants were enthusiastic about gaining knowledge from attending this training, and hoped that there would be further training that would equip them with other new knowledge.